Frictionless flow in channels - Koh, Wee Liang. (2011)
Over the past few decades, since the emergence of lotus leaves and its self-cleaning abilities, many research and studies are conducted to study the factors affecting the hydrophobicity of a surface. Fluid flow in micro channels is one of the major areas that are gaining importance for its technological breakthrough. The slip and no-slip boundary condition in micro channels remain one of the topic still being greatly debated despite countless studies. The project aims to study the interactions between solid-water interfaces as fluid flow through microchannels. Over the years, researches were done extensively on the slip and no-slip models based on experiments and theoretical study. Prior to this, experiments were conducted and many equations were derived. Comparisons between theoretical values and experimental results are done to substantiate the accuracy of the models and determine which models best fit the real life experiments. Nonetheless, both experiments and analytical approach have their own shortcomings. Conducting experiments are expensive and time consuming. Furthermore, certain experiments are avoided for safety reasons. Analytical approach usually involves solving equations too complex to analyze. Moreover, it involves assumptions not applicable to real-world phenomena. All these shortcomings can be solved by using numerical simulation approach. In numerical simulation, models are developed and results are computed in relatively short time span. The overall project includes comparison of the numerical simulation results to theoretical and experimental data in order to obtain a clearer picture of which models fit more closely to the real life experiments.